Borys Pasternak w polskiej konspiracji - Mitzner, Piotr (Colloquia Litteraria, 2018)
The paper focuses on the editorial history of the volume of poetry by Borys Pasternak entitled Siedem wierszy [Seven poems], which was published in Warsaw in 1940, that is during the German occupation of the city.